Elizabeth Jaquelin Ambler Brent Carrington papers - Carrington, Elizabeth Jaquelin Ambler Brent, 1765-1847.
Volume (30 items) containing letters addressed to various female correspondents, describing daily social life, travel, and education in late 18th and early 19th century Virginia. Includes references to her husbands, William Brent and Edward Carrington, her brother-in-law, John Marshall, and George Washington.
Born Elizabeth Jaquelin Ambler; married first William Brent; second, Edward Carrington.
Negative photocopies produced from originals in the hands of Carter Fitz-hugh.
Colonial Williamsburg Foundation
Collection material in English.
Keywords: Brent, William, -- 1733-1782.; Carrington, Edward, -- 1749-1810.; Marshall, John, -- 1755-1835.; Washington, George, -- 1732-1799.; Education -- Virginia; Women; Virginia -- Description and travel; Virginia -- Social life and customs